ANALISIS REGULASI PREDATORY PRICING DALAM BISNIS DIGITAL DI INDONESIA PERSPEKTIF HUKUM ISLAM - Arif Fikri; Rahayu Utami Caniago; Ramos Panggabean; Abdul Azis Lasahido (Adpertens: Jurnal Ekonomi dan Manajemen, 2026)
This study analyzes regulations concerning predatory pricing practices in digital businesses in Indonesia from an Islamic law perspective. Predatory pricing is a strategy of setting extremely low prices to eliminate competitors, potentially harming other businesses and consumers. The research employs a qualitative field-based approach, collecting data through in-depth interviews with 12 digital business actors, 5 regulatory officials, and document analysis of regulations and fatwas issued by the Indonesian Ulama Council (MUI) regarding business ethics. Thematic analysis with source triangulation was applied to ensure the validity of findings. The results indicate that predatory pricing practices still occur, particularly during market penetration stages, despite existing anti-monopoly regulations. From the perspective of Islamic law, this practice contains elements of gharar (uncertainty) and dzulm (injustice) because it creates unfair conditions for other business actors and consumers. The study also identifies a gap between formal regulations and their implementation in the field, including weak supervision and insufficient sanctions against violators.